Juvenile Dungeness crabs (Metacarcinus magister) selectively integrate and modify the fatty acids of their experimental diets. (3rd August 2020) - Thomas, Michael D.; Schram, Julie B.; Clark-Henry, Zade F.; Yednock, Bree K.; Shanks, Alan L.; Galloway, Aaron W. E.
Abstract : Dungeness crabs ( Metacarcinus magister ) are ecologically and economically important in the coastal Northeast Pacific, yet relatively little is currently known about their feeding behaviour in the wild or their natural diet. Trophic biomarkers, such as fatty acids (FA), can be used to reveal trophic interactions. We used two feeding experiments to assess differences in FA composition of juvenile crabs fed different known foods to evaluate how they modify and integrate dietary FA into their own tissues and determine whether crab FA reflect diet changes over a six-week period. These experimental results were then compared with the FA signatures of wild caught juvenile crab with undetermined diets. We found that juvenile Dungeness crabs fed different foods assimilated dietary FA into their tissues and were distinct in their FA signatures when analysed with multivariate statistics. Experimentally fed juvenile crabs contained greater proportions of the most abundant long-chain polyunsaturated fatty acids (LCPUFA, >C20) than their foods. Crabs fed foods lacking in LCPUFA, particularly DHA (22:6 ω 3, docosahexaenoic acid), did not survive or grew slower than crabs fed other foods. This suggests that LCPUFA are physiologically important for this species and indicates biosynthesis of these FA does not occur or is not sufficient to meet their needs. This article is part of the theme issue 'The next horizons for lipids as 'trophic biomarkers': evidence and significance of consumer modification of dietary fatty acids'.